Spray-Drying of Hydroxypropyl β-Cyclodextrin Microcapsules for Co-Encapsulation of Resveratrol and Piperine with Enhanced Solubility - Yang, Xing; Shen, Jian; Liu, Jia; Yang, Yuxin; Hu, Anna; Ren, Na; Cheng, Zeneng; Liu, Wenjie (Crystals (Basel), 2022)
The synergistic therapeutic benefits of resveratrol (RES) and piperine (PIP) have been proven for the treatment of various diseases. This study reports, for the first time, spray-drying of hydroxypropyl β-cyclodextrin (HP-β-CD) microcapsules for combined delivery of resveratrol and piperine. Phase solubility studies indicated that there was a strong interaction between the active ingredients and HP-β-CD, and both active ingredients can bind stably to HP-β-CD. The results of FTIR, XRD, and DSC demonstrated that RES-PIP/HP-β-CD inclusion complexes were successfully formed, with the RES and PIP encapsulated into the hollow spherical cavity of HP-β-CD. The results of SEM showed that the spray-dried microcapsules displayed a smooth surface and uniform particle size. Upon the formation of the spray-dried microcapsules, both RES and PIP presented significantly enhanced solubility. The results of DPPH and ABTS+ scavenging activity assays showed that the spray-drying process did not adversely influence the antioxidant activity of the bioactives, and the addition of PIP increased the antioxidation performance of RES.